METTL3 Contributes to Osteosarcoma Progression by Increasing DANCR mRNA Stability via m6A Modification - Zhou, Xinying; Yang, Yang; Li, Yuejun; Liang, Guojun; Kang, Dawei; Zhou, Bing; Li, Qingchu (Frontiers in Cell and Developmental Biology, 2022)
Background: Osteosarcoma (OS), known as the most prevalent bone cancer among children and adolescents, exhibits a relatively high mortality. RNA N6-methyladenosine (m6A), as the most common modification of human mRNA, exerts diverse functions in a variety of biological processes. Previous studies have documented that methyltransferase-like 3 (METTL3), the first identified methyltransferase, could act as oncogene or tumor suppressor on multiple human cancers. However, its function and underlying mechanism in OS progression have not been fully documented. Therefore, we aimed to explore the function and the molecular mechanism of METTL3 in OS progression. Methods: RT-qPCR and western blot analysis of METTL3 expression in OS tumor tissues and five OS cell lines were performed and its clinical significance was also explored. To further examine the functional role of METTL3 in OS progression, CCK-8 analysis, transwell assay and xenograft model were carried out after silencing of METTL3. Additionally, the underlying mechanism was explored by analysis of RIP-seq, RIP-qPCR, RT-qPCR, CCK-8 experiment, transwell assay and western blot. Results: We found METTLE3 was upregulated in OS tumor tissues and cell lines and associated with worse prognosis. Moreover, silencing of METTL3 suppressed the proliferation, migration and invasion of OS cells. Also, in vivo oncogenic function of METTL3 was confirmed by the xenograft model. A deeper mechanism study revealed lncRNA DANCR could be a potential target of METTL3, confirmed by a reduced level of DANCR after METTL3 silencing. Concordantly, lncRNA DANCR knockdown repressed OS cells proliferation, migration and invasion. Furthermore, silencing of both METTL3 and lncRNA DANCR could significantly suppressed the growth and metastasis of OS. Finally, we suggested METTL3 regulated DANCR expression through m6A modification-mediated DANCR mRNA stability. Conclusion: Our studies documented METTL3 contributes to OS progression by increasing DANCR mRNA stability via m6A modification, thus indicating that METTL3 is a promising therapeutic target for the treatment of OS.